2015
DOI: 10.1634/theoncologist.2014-0453
|View full text |Cite
|
Sign up to set email alerts
|

Poor Awareness of Risk Factors for Cancer in Irish Adults: Results of a Large Survey and Review of the Literature

Abstract: Background. Knowledge of cancer risk factors is unknown inIreland. An understanding of risk factors could help inform cancer prevention programs. Aims and Methods. A 48-question online survey was designed to gather data to assess levels of public knowledge about cancer risk factors.Results. There were 748 participants (648 women, 100 men). Mean age was 37 years (range: 18-74 years). For the public, 81% were concerned about developing cancer; however, 20% believed that cancer is unavoidable if a family history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 43 publications
5
54
0
1
Order By: Relevance
“…For example, less than one‐quarter of our sample were aware of specific types of cancer. This is consistent with low rates of awareness of alcohol as a risk factor for cancer in other studies 9–12 . Surprisingly, one‐third of the sample did not say that harm to unborn babies was a consequence of alcohol use.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, less than one‐quarter of our sample were aware of specific types of cancer. This is consistent with low rates of awareness of alcohol as a risk factor for cancer in other studies 9–12 . Surprisingly, one‐third of the sample did not say that harm to unborn babies was a consequence of alcohol use.…”
Section: Discussionsupporting
confidence: 85%
“…8 Typically, there is a low awareness among adult drinkers of the harmful consequences of alcohol use. For instance, it is estimated that 14%-48% of drinkers list alcohol as a risk factor for cancer, [9][10][11][12] between 5% and 79% of drinkers are aware that alcohol is a risk factor for heart disease, 10,11,13 and 20%-27% are aware is it linked to an increased risk of stroke. 14,15 However, one Australian study indicates a near perfect (98% of their sample) awareness of the link between alcohol use and liver problems.…”
mentioning
confidence: 99%
“…Studies indicate that, over the past decade, 25% of all cancers could be prevented by reducing the rate of obesity [1315]. …”
Section: Mediterranean Diet Metabolic Syndrome (Mets) and Obesitymentioning
confidence: 99%
“…Our study population had a relatively high awareness of cancer risk factors at baseline, as compared to the general population . For example, 72% of our study population was aware of overweight as a cancer risk factor, while this was reported for only 52% of the general population in the US .…”
Section: Discussionmentioning
confidence: 76%